La valorizzazione economica del patrimonio artistico delle città d'arte - Lazzeretti, Luciana (Firenze University Press, 2001)
This book addresses the issue of the potential economic significance of the artistic heritage in an art city - more specifically Florence - taking as a concrete example for the purpose of scientific research the figure of the "artistic restorer" in the dual garb of economic agent and environmental and cultural resource for the city. The empirical study of the private firms working in this sector located in the Florence area is accompanied and introduced by a broad analysis of the policies for protection and enhancement of the cultural assets, and of the economic, non-economic and institutional agents involved in the same.